Effect of silencing SSB1 gene on the expression of NBS1 in irradiated rat submandibular gland cells: Silencing SSB1 gene: SD male rat submandibular gland - Gao, Linjing; Lv, Qiuli; Huang, Yude; Fan, Yiyang; Zhao, Lixiang; Zhao, Yanfei; Wang, Xian; Mo, Dongqin; Lu, Haoyu; Wang, Daiyou (Cellular and Molecular Biology, 2024)
The salivary gland (SGS) is a kind of organ vulnerable to ionizing radiation. Radiotherapy is an important treatment for head and neck tumors, but in the process of radiotherapy, tumor cells will be injured by radiation to a certain extent. Infrared-induced DNA double-strand break (IR-DSBs) is one of the most serious DNA damage. DNA repair proteins such as Nymegan rupture syndrome protein 1 (NBS1) play a key role in the identification and repair of DNA damage. but the interaction between SSB1 and NBS1 has not been elucidated. In this study, we irradiated rat submandibular gland (SMG) cells, which were either infected with a rAdE5-SSB1-1p2-shRNA recombinant adenovirus to silence SSB or a control virus, to explore the effect of IR on the expression NBS1 in the absence of SSB. Our results showed that the SSB1 mRNA transcripts and protein expression of SSB1 and NBS1 initially increased and decreased later with increased doses. The relative expression reached the highest levels when the SMG cells were irradiated with 2Gy of IR. Silencing the SSB1 gene suppressed the expression of both SSB1 and NBS1 regardless of irradiation. The expression of NBS1 decreased when the SSB1 gene was silenced. We concluded that IR affected the expression of both SSB1 and NBS1 and there is a synergistic effect on IR-induced NBS1 suppression and DSBs repair in SMG cells. These observations shed light on further investigation and elucidation of IR-caused DNA repair mechanisms.